Primary Spindle Cell Sarcoma of the Breast - Cil, Timucin (S. Karger GmbH, 2008)
BACKGROUND: Primary pure breast sarcoma is a rare disease and constitutes 0.2–1.0% of all mammary malignancies. The establishment of a diagnosis of soft tissue sarcoma is difficult in adults. Immunohistochemical analysis usually proves to be helpful in indistinguishable cases. The simplistic step is to classify sarcomas on a simple descriptive basis as spindle cell sarcomas, myxoid sarcomas, pleomorphic sarcomas, and small round cell sarcomas. CASE REPORT: Here, we present a rare case of primary spindle cell sarcoma of the breast. A 43-year-old woman was admitted to our clinic with a 2-month history of a left breast lump. Histopathological examination showed a tumor of 2.5 cm in diameter and of nuclear and histological grade 2. In the immunohistochemical examination, vimentin positivity, high nuclear overexpression of P53, high Ki-67 and S-100, desmin, leukocyte common antigen, keratin, and smooth muscle antigen, CD34, HMB45 and EMA negativity were detected. CONCLUSION: Most invasive breast neoplasms are epithelial tumors, and mesenchymal breast tumors are rarely seen. In primary breast sarcoma, adequate surgical tumor excision, tumor grade, and tumor diameter seem to be the most important prognostic factors.